Pelatihan dan Sosialisasi Kewirausahaan Digital Paska Pandemi COVID-19 Bagi Generasi Muda Sekitar Gereja El-Shaddai Surabaya - Hariyanti, Novi Tri; Wirapraja, Alexander; Sutjiadi, Raymond; Setyoadi, Eddy Triswanto (Jurnal Dharma Bhakti Ekuitas, 2023)
Entrepreneurship and self-reliance are important points for the Indonesian people in improving their economic standard of living, especially during the current post-COVID-19 recovery period. Many people have been affected by the COVID-19 pandemic, especially on the economic side, causing a decline in people's income and standard of living. This digital entrepreneurship training program was carried out at the El-Shaddai church in Surabaya, targeting community groups that were economically affected by COVID-19. The purpose of this activity is to provide knowledge and training regarding the use of digital media in marketing the products they already have. In addition to training, regular assistance is also provided to ensure the success of this program and have a direct impact on community service partners. The implementation of the program is carried out by a team consisting of lecturers as facilitators and students as assistant facilitators. The results obtained show that people are getting used to doing product management and utilizing digital media such as social media and marketplaces to market their products. Keywords: Assistance, digital marketing, entrepreneurship, training. Abstrak Kewirausahaan dan kemandirian menjadi poin penting bagi masyarakat Indonesia dalam meningkatkan taraf hidup ekonomi mereka khususnya dalam masa pemulihan paska pandemi COVID-19 saat ini, banyaknya masyarakat yang terdampak pandemi COVID-19 khususnya pada sisi ekonomi menyebabkan menurunnya pendapatan dan taraf hidup masyarakat. Program pelatihan kewirausahaan digital ini dilaksanakan di gereja El-Shaddai Surabaya dengan menyasar pada kelompok masyarakat yang terdampak COVID-19 secara ekonomi. Tujuan kegiatan ini adalah memberikan pengetahuan dan pelatihan mengenai penggunaan media digital dalam memasarkan produk yang sebenarnya sudah mereka miliki, selain pelatihan juga dilakukan pendampingan secara berkala untuk memastikan keberhasilan dari program ini dan berdampak langsung kepada masyarakat mitra pengabdian. Pada pelaksanaan program dilakukan oleh tim yang terdiri dari dosen sebagai fasilitator dan mahasiswa sebagai asisten fasilitator. Hasil yang didapatkan adalah masyarakat mulai terbiasa dalam melakukan manajemen produk dan memanfaatkan media digital seperti media sosial dan marketplace dalam memasarkan produk mereka. Kata kunci: pendampingan, pemasaran digital, kewirausahaan, pelatihan.